The Emergence of Wakhan Fortresses in the Hellenistic Period - Lerner, Jeffrey D. (Anabasis. Studia Classica et Orientalia, 2016)
The Wakhan Highway situated along the Pianj on the upper reaches of the Amudaria, was one the main roads that ran through the western Pamir until the Arab conquest. It stands out for the cultural and historical role it played as a crucial link in the transasiatic route allowing travelers to pass through western China in the north and Afghanistan and India in the south. A series of fortresses line the bank of the northern bank of the Pianj in modern Tajikistan. The region long populated by Saka tribes may have been part of the twelfth satrapy of the Achaemenid Empire. Fortresses, like Kaakhka I and Yamchun I, dating back to the Greek-Baktrian Period served as bulwarks against nomadic tribes migrating southward. While the region remained part of the Greek-Baktrian kingdom either by conquest or by alliance, most of these castles appear to have been renovated or constructed by the Kushans, but not against the possible encroachment of the nomadic Sakai, but against a more powerful foe, the Han Chinese.